Dopant concentration and thermoluminescence (TL) properties of tailor-made Ge-doped SiO2 fibres - Zahaimi, Nurul Arina; Abdullah, Mohd Haris Ridzuan Ooi; Zin, Hafiz; Abdul Rahman, Ahmad Lutfi; Hashim, Suhairul; Saripan, Mohd Iqbal; Paul, Mukul Chandra; Bradley, D. A.; Abdul Rahman, Ahmad Taufek (Elsevier, 2014)
Study focuses on characterisation of diverse concentrations of Ge-doped SiO2 fibre as a potential thermoluminescence (TL) system for radiotherapy dosimetry. Irradiations were made using a linear accelerator providing 6 MV and 10 MV photon beams. Investigation has been done on various doped core diameter Ge-doped SiO2 glass fibres such as commercial telecommunication fibres of 8 µm and 9 µm (CorActive High Tech, Canada), tailor-made fibres of 23 and 50 µm produced by the Central Glass and Ceramic Research Institute Kolkata, and tailor-made fibres of 11 µm produced by the University of Malaya Photonics Research Centre. The fibres have been characterised for TL sensitivity, reproducibility, dose- and energy-dependence. The area under the TL glow curve increases with increasing core diameter. For repeat irradiations at a fixed dose the dosimeter produces a flat response better than 4% (1SD) of the mean of the TL distribution. Minimal TL signal fading was found, less than 0.5% per day post irradiation. Linearity of TL has been observed with a correlation coefficient (r2) of better than 0.980 (at 95% confidence level). For particular dopant concentrations, the least square fits show the change in TL yield, in counts per second per unit mass, obtained from 50 µm core diameter fibres irradiated at 6 MV of photon to be 8 times greater than that of 8 µm core diameter fibre. With respect to energy response, the TL yield at 10 MV decreases by~5% compared to that at 6 MV, primarily due to the lower mass energy absorption coefficient at higher photon energy. These early results indicate that selectively screened fibres can be developed into a promising TL system, offering high spatial resolution capability and, with this, verification of complex radiotherapy dose distributions.